Letramento literário no ensino médio: o que propõem livros didáticos? - Luciana Mara Torres (2015)
The National Textbook Program for High School completed, in 2015, ten years running, with four editions. Its research was based on discussions about literary literacy, training players and the social function of literature to reflect on the teaching of literature in high school, from textbooks that come to public schools through The National Textbook Program for High School. Thus, by analyzing these materials, our goal was to get closer to an answer to the following question: What proposals of literary education have shown Portuguese textbooks to high school in the last years? To answer this question, we analyzed the official guiding documents of high school in Brazil, like the Curriculum Standards (1999) and the Curriculum Guidelines (2006), focusing on the literature of education. This analysis showed that literature was gaining ground in discussions among researchers and developers of these documents. The literary literacy term became prominent and the teaching of literature focused on literary schools, should, according to the experts, give way to the literary reading. In addition, we analyzed The National Textbook Program for High School guides from two editions, in 2006 and 2015 in order to verify which criteria for Literature Education were used choosing textbooks and made available to the public education. From them we established categories of analysis of the textbooks: Organization; textual collection; activities, literature dialogue with another arts. Given these categories, we study the chapters focused on the teaching of literature in two different editions of textbook collections approved in the 2006 and 2015 editions. We presented the approaches and the distances between them, showing what has changed and what has remained in literatures teaching in the space of ten years, also considering the changes in the official documents.